Multidrug resistant tuberculosis in prisons located in former Soviet countries: A systematic review. - Maxwell Droznin; Allen Johnson; Asal Mohamadi Johnson (PLoS ONE, 2017)
Background A systematic literature review was performed to investigate the occurrence of multidrug-resistant tuberculosis (MDR TB) in prisons located in countries formerly part of the Soviet Union. Methods A systematic search of published studies reporting MDR TB occurrence in prisons located in former Soviet countries was conducted by probing PubMed and Cumulative Index Nursing and Allied Health Literature for articles that met predetermined inclusion criteria. Results Seventeen studies were identified for systematic review. Studies were conducted in six different countries. Overall, prevalence of MDR TB among prisoners varied greatly between studies. Our findings suggest a high prevalence of MDR TB in prisons of Post-Soviet states with percentages as high as 16 times more than the worldwide prevalence estimated by the WHO in 2014. Conclusion All studies suggested a high prevalence of MDR TB in prison populations in Post-Soviet states.